The Billionaire's Island Bride - Alward, Donna (Alward, Donna. South Shore billionaires, 2020)
She can't resist him......but can she trust him--with her heart? Brooklyn Graves's blissfully peaceful if solitary existence is threatened when billionaire Cole Abbott wants to buy her corner of their shared private island. She'll never sell! But she quickly comes to enjoy sharing intimate evenings--and even more intimate secrets--with Cole... And what Brooklyn soon realizes she wants from Cole is something money can't buy--his love.